Limits to alternative forms of capitalization: The case of Anatolian holding companies - ÇOKGEZEN, MURAT (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Since the late 1960s, alternative forms of capitalization have emerged in the absence of an effective capital markets regime in Turkey. We can see these alternative forms in the failed attempts to create Anatolian holding companies through the direct investment of small savings. This article shows how Anatolian holding companies became victims of poor institutional and regulatory regimes, and how the lack of institutions to promote impersonal trust in the economy in turn, permitted widespread abuses. We identify populist politics, lax oversight, and social norms that incorporated gambling as three interlinked reasons which hindered the genesis and development of viable capital market reform and regulatory institutions in Turkey. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: capital formation; financial markets; state regulation; Anatolian holding companies; Islamic finance; Turkey; OWNERSHIP; POLITICS; TURKEY; COSTS; FIRM